EKSPLORASI PENGALAMAN GURU DALAM MENGEMBANGKAN PERANGKAT PEMBELAJARAN DI SEKOLAH DASAR - Rizki Eka. S; Muhammad Sofwan; Desy Rosmalinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teachers’ experiences in developing instructional materials through four indicators: technique, process, feelings, and outcomes. Employing a qualitative phenomenological approach, the research was conducted at SD Negeri 96/IV Kota Jambi during the 2025/2026 academic year with experienced teachers as participants. Data were collected through interviews and documentation and validated using source triangulation. The findings show that in the technique aspect, teachers demonstrate a strong understanding of the importance of instructional materials and develop them systematically in alignment with curriculum objectives. In the process aspect, teachers conduct diagnostic assessments to adjust materials based on students’ needs and apply innovative strategies supported by concrete media and educational technology. In the feelings aspect, teachers express positive emotions such as pride, satisfaction, and motivation, which enhance their confidence and pedagogical competence. In the outcomes aspect, the instructional materials developed by teachers contribute to improved teaching quality, better student learning outcomes, and strengthened professional reflection. Overall, these experiences positively influence instructional effectiveness and support teacher professionalism.